“Proximity,” representation and participation. The Participatory Budget in Argentina - Annunziata, Rocío (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2011)
This article conceives ‘proximity’ as an emerging form of legitimacy, and the so-called ‘participatory mechanisms’ as their institutional crystallization. In the first part, the author proposes a characterization of the proximity principle; then, based on field work in the Argentine municipalities of Morón, Rosario and the City of Buenos Aires, demonstrates how the participatory mechanism, and especially the Participatory Budget, bring into play transformations in political legitimacy. The article demonstrates how the Participatory Budget institutionalizes a politics of the singularity of experience: in addition to the legitimacy of political party, collective-redistributive and technical or expert knowledge, there operates the legitimacy of the neighbor’s concrete problems, the micro-territory, and knowledge based on daily experience. Finally and based on this points, the author raises the question of contradiction, complementarity and interiority between representation and participation.